ANALISIS PELEBARAN JALAN SEBAGAI STRATEGI PENINGKATAN KAPASITAS, KESELAMATAN, DAN EFISIENSI TRANSPORTASI DI KABUPATEN PALI - Andri Wirawan; Kiagus Muhammad Aminuddin; David Bahrin (LATERAL: Jurnal Teknik Sipil, 2026)
Road widening is a key strategy to improve traffic capacity and transportation service quality. However, integrated evaluations that simultaneously address capacity, safety, and economic benefits remain limited. This study aims to analyze the impact of widening the Simpang 3 Talang Subur – Talang Kemang road section in Penukal Abab Lematang Ilir Regency on traffic capacity, road safety, and economic efficiency. Primary data were collected through an Average Daily Traffic (ADT) survey using the traffic counting method, while secondary data included vehicle growth records and traffic accident statistics. Capacity analysis was conducted based on the Indonesian Highway Capacity Manual (PKJI) 2023 by comparing existing conditions (5 m road width) with a widening scenario (7.2 m). The results show a significant increase in capacity from 1,494 smp/hour to 2,668 smp/hour, accompanied by an improvement in level of service from LOS E to LOS C. Projections indicate that post-widening capacity will accommodate traffic growth for the next 10 years. In terms of safety, widening may increase vehicle speeds, highlighting the need for traffic control and supporting facilities. Economically, benefits were assessed through Travel Time Savings (TTS), demonstrating substantial transport cost efficiency.